Optimasi Optical Density (OD) Dan Dosis Kanamisin Dalam Transformasi Gen Sucrose Phosphate Synthase (SoSPS1) Pada Anggrek Dendrobium sp. - Arsy Chairiyah; Bambang Sugiharto; Purnama Okviandari; Parawita Dewanti; Khiar Ayatina Hasbi (Universitas Gadjah Mada, 2025)
Genetic transformation in plants involves the insertion of isolated foreign genes into the plant genome. Sucrose Phosphate Synthase (SPS) is a key enzyme in sucrose biosynthesis, the primary sugar serving as an energy source and carbon transport molecule in most plants. Dendrobium orchids, which utilize Crassulacean Acid Metabolism (CAM), often exhibit a slow growth rate, thereby limiting their commercial potential. The insertion of the SPS gene into the orchid genome is expected to optimize the sucrose metabolic pathway, potentially influencing the rate of photosynthesis, carbon allocation, and growth characteristics of the orchid. Optimizing the optical density (OD) of the Agrobacterium suspension and the dosage of kanamycin is crucial for enhancing the success rate of the gene transformation process. This study aimed to determine the optimal concentrations of OD and kanamycin to achieve efficient SoSPS1 gene transformation in orchids. Three-month-old Protocorm-Like Bodies (PLBs) of Dendrobium Glory White were used as the explant source. The transformed explants were subsequently evaluated for the effectiveness of the kanamycin dosage, the percentage of explant shoots, the number of shoots per explant, the transformation efficiency, and phenotypic changes in the transformed plants. The results showed that a transformation efficiency of up to 40% was achieved using an Agrobacterium suspension at an OD600nm of 0.4. A lethal dose (LD50) of 100 mgL-1 kanamycin resulted in 34% of plantlets surviving post-selection. Transformation with the SoSPS1 gene in Dendrobium sp. induced distinct phenotypic plants including split leaves, swollen stems (pseudobulb), and increased shoot multiplication.